Assessment of different organic coatings on magnetic nanoparticles for biomedical applications - Zainon, Nur Khalida Rahayu; Che Abdullah, Che Azurahanim; Abdul Rahman, Mohd Basyaruddin (Inderscience Publishers, 2024)
Magnetic nanoparticles (MNPs) are well-known for unique magnetic properties, excellent biocompatibility, and targeting specialty, making them an unmatched gem for use in nanomedicines. However, naked MNPs are susceptible to oxidation, are hydrophobic by nature, and are intrinsically unstable. As a result, stabilisers such as surfactant and polymer are required to protect against particle aggregation and degradation. Additionally, depending on the application, surface coatings facilitate further functionalisation with additional nanoparticles, ligands, or therapeutic agents. This work employed the controlled synthesis and coating of MNPs with organic coatings. The nanoparticles' surfaces were coated with a lipid-based oleic acid surfactant (OA) and a polymer-based poly(ethylene glycol) (PEG). The nanoparticles were synthesised via co-precipitation and then coated with different ratios of organic materials before being subjected to a variety of characterisation tools. The purity of the magnetite was confirmed using XRD analysis and revealed a decrease in crystallinity as the coating agent concentration increased. Optical (FTIR) and mechanical properties (TGA) measurements established the presence of the coating on MNPs. VSM characterisations revealed that both coated MNPs samples showed superparamagnetic properties with high magnetic saturation (Ms) which is ideal for biomedical applications. TEM data showed uniform spherical morphology and exhibited decrease in average particle size for coated MNPs.